Vascular Notch Signaling in Stress Hematopoiesis - Huang, Can; Yang, Dawei; Ye, George W.; Powell, Charles A.; Guo, Peipei (Frontiers in Cell and Developmental Biology, 2021)
Abstract Canonical Notch signaling is one of the most conserved signaling cascades. It regulates cell proliferation, cell differentiation and cell fate maintenance in a variety of biological systems during development and cancer (Fortini, 2009; Kopan and Ilagan, 2009; Andersson et al., 2011; Ntziachristos et al., 2014). For the hematopoietic system, during embryonic development, Notch1 is essential for the emergence of hematopoietic stem cells (HSCs) at the aorta-gornado-mesonephro regions of the dorsal aorta. At adult stage, Notch receptors and Notch targets are expressed at different levels in diverse hematopoietic cell types and influence lineage choices. For example, Notch specifies T cell lineage over B cells. However, there has been a long-lasting debate whether Notch signaling is required for the maintenance of adult HSCs, utilizing transgenic animal inactivating different components of the Notch signaling pathway in HSCs or niche cells. The aim of the current mini-review is to summarize the evidence that disapproves or supports such hypothesis, and point at imperative questions awaiting to be addressed, hence, some of the seemingly contradictory findings could be reconciled. We need to better delineate the Notch signaling events using biochemical assays to identify direct Notch targets within HSCs or niche cells in specific biological context. More importantly, we call for more elaborate studies it pertains to whether niche cell type (vascular endothelial cells or other stromal cells)-specific Notch ligands regulate the differentiation of T cells in solid tumors, and during the progression of T-ALL or CMML. We believe that the investigation of vascular endothelial cells or other stromal cell types interaction with hematopoietic cells during homeostasis and stress can offer insights toward specific and effective Notch-related therapeutics.